IMPLEMENTASI PERANGKAT LUNAK UNTUK PENENTUAN ALAT KONTRASEPSI DENGAN METODE PENDEKATAN ANALYSIS HIERARCHY PROCESS (AHP) - Sri Winarno; Sumardi Sumardi; Rosana Podesta (VISIKES: Jurnal Kesehatan Masyarakat, 2011)
Background: Over the last ten years (2000-2010), Indonesia’s population growth rate per year was increase. It becomes a problem for government. Family Planning program is one solution to solve this problem. The mission of family planning is to achieve a small happy family prosperous counseling about family planning and contraceptive devices are important. The developmentand improvement of counseling and services to achieve family planning goals should be taken continuously. Decision Support System helps people in choosing best contraception fits their health condition. Every people have differences characteristics to apply the contraceptiveuse. So, they could not imitate others to use contraception. The study aims to develop counseling and services based decision support system that can help family planning acceptors in choosing the best contraceptive method for himself by using Analysis Hierarchy Process (AHP). It expected to provide quick and precise information at any time in order to make decisions in choosing a suitable contraceptive and safe for users.Keywords: Analysis Hierarchy Process (AHP), contraceptive use